2019
DOI: 10.1016/j.adolescence.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the association of neighborhood ethnic‐racial concentrations and adolescent behaviour problems in the U.S.

Abstract: Introduction: Evidence suggesting a link between neighborhood ethnic-racial concentrations and adolescent behaviour problems in the U.S. is mixed, with some studies documenting negative and others positive associations. This work raises important questions about promoting and inhibiting efects of neighborhood environments characterized by high concentrations of ethnic-racial minority groups, including Asian Americans, Blacks or African Americans, and Latinos. We conducted a meta-analysis to examine 1) the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Specifically, additional studies on adolescent development are needed from non‐western countries. We also applaud White, Pasco, Korous, & Causadias, 2020 discussion of the need for future research on sub‐group ethnic/racial differences. The articles in this special issue also highlight the need for multiple‐informant research methods.…”
Section: Methodological Considerationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Specifically, additional studies on adolescent development are needed from non‐western countries. We also applaud White, Pasco, Korous, & Causadias, 2020 discussion of the need for future research on sub‐group ethnic/racial differences. The articles in this special issue also highlight the need for multiple‐informant research methods.…”
Section: Methodological Considerationsmentioning
confidence: 94%
“…Moreover, these effects were more pronounced in younger adolescents compared to older adolescents. Within a similar moderation framework, White, Pasco, Korous, & Causadias (2020) found that the effect of neighborhood racial‐ethnic concentration on adolescent behavior problems was, on average, zero. Moreover, the substantial variability in effect sizes across studies was not explained by study characteristics or neighborhood measure.…”
Section: Methodological Considerationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Extant findings relative to neighborhood Latinx concentration and child mental health are mixed. A recent meta-analysis found that Latinx concentration was associated with fewer mental health problems in about half of the studies and more mental health problems in the other half; the authors argued for more developmentally and culturally informed work with greater diversity of data sets (White, Pasco, Korous, & Causadias, 2020). From a culturally informed developmental perspective (Garc ıa Coll et al, 1996), mixed findings may stem from individual differences in ethnicity.…”
mentioning
confidence: 99%